Antinociceptive and anti-inflammatory effects of the ethanol extract of Alpinia conchigera Griff. leaves in various animal models - Sulaiman, Mohd Roslan; Zakaria, Zainul Amiruddin; Adilius, M.; Mohamad, Azam Shah; Ismail, Maznah; Israf Ali, Daud Ahmad (Prous Science, 2009)
The ethanolic extract of Alpinia conchigera Griff. leaves (EACL) was evaluated for its antinociceptive and anti-inflammatory activities in several in vivo experimental models. Antinociceptive activity was determined using the acetic acid-induced abdominal writhing test, the hot plate test and the formalin test. Anti-inflammatory activity was determined using the carrageenan-induced paw edema test. The extract (30, 100 and 300 mg/kg i.p.) was found to possess significant, dose-dependent inhibitory activity in all test models. In addition, the antinociceptive effect of the extract in the acetic acid-induced writhing and hot plate tests was reversed by naloxone, suggesting that this activity is mediated through activation of the opioid system. These findings suggest that EACL presents notable analgesic and anti-inflammatory activities, which support its folkloric use for painful and inflammatory conditions.